Household chores and household choices : theorizing the domestic sphere in historical archaeology - Barile, Kerri S.; Brandon, Jamie C. (University of Alabama Press, 2004)
The time is ripe for such an effort, as the questions that gather under the labels of modernity, the postmodern, and critical theory now transcend a single discipline. The work of John Rawls on justice in public life has had a generation of influence on scholarship, and this work seems to have a high degree of likelihood of making meaningful statements on these questions in the field.